The autobiography of Eleanor Roosevelt. - Roosevelt, Eleanor, 1884-1962 (New York : HarperCollins, 2014)
A candid and insightful look at an era and a life through the eyes of one of the most remarkable Americans of the twentieth century The long and eventful life of Eleanor Roosevelt (1884-1962) was full of rich experiences and courageous actions. The niece of Theodore Roosevelt, she married a Columbia University law student named Franklin Delano Roosevelt, who gradually ascended in the world of New York politics to reach the presidency in 1932. Throughout his three terms, Eleanor Roosevelt was not only intimately involved in FDR's personal and political life but also led women's organizations and youth movements, and fought for consumer welfare, civil rights, and better housing standards. During World War II she traveled with her husband to meet leaders of many powerful nations; after his death in 1945 she worked as a UN delegate, chairman of the Commission on Human Rights, newspaper columnist, Democratic Party activist, and diplomat, and was a world traveler. By the end of her life, Eleanor Roosevelt was recognized around the world for her fortitude and commitment to the ideals of liberty and human rights. Her autobiography constitutes a self-portrait no biography can match for its candor and liveliness, wisdom, tolerance, and breadth of view--a self-portrait of one of the greatest American humanitarians of our time. With 8 pages of black-and-white photographs and an afterword by Eleanor Roosevelt's granddaughter
pt. I. This is my story. Memories of my childhood ; Adolescence ; Home again ; Early days of our marriage ; A woman ; My introduction to politics ; Washington ; Growing independence ; A changing existence ; Readjustment ; The 1920 campaign and back to New York ; Trial by fire -- pt. II. This I remember. The private lives of public servants ; Private interlude : 1921-1927 ; The governorship years : 1928-1932 ; I learn to be a president's wife ; The first year : 1933 ; The peaceful years : 1934-1936 ; Second term : 1936-1937 ; The royal visitors ; Second term : 1939-1940 ; The coming of war : 1941 ; Visit to England ; Getting on with the war : 1943 ; Visit to the Pacific ; Teheran and the Caribbean ; The last term : 1944-1945 -- pt. III. On my own. An end and a beginning ; Not many dull moments ; Learning the ropes in the UN ; I learn about Soviet tactics ; The Human Rights Commission ; Foreign travels ; The long way home ; Campaigning for Stevenson ; Bali and Morocco ; In the land of the Soviets ; A challenge to the West -- pt. IV. The search for understanding. Second visit to Russia ; The American dream ; Milestones ; The Democratic Convention of 1960 ; Unfinished business.
Includes index.
A hardcover edition of this book was originally published in 1961 by Harper & Brothers.
Keywords: Roosevelt, Eleanor, -- 1884-1962.; Presidents' spouses -- Biography; Roosevelt, Eleanor, -- 1884-1962.; Presidents' spouses; Biography